Challenges in the operation and maintenance of assets and facilities in elderly care centres in Malaysia - Mohd Tombel, Nor Syahila; Mohyin, Nur Affah; Ayob, Mohd Fairullazi (2024)
Abreast with the rapid growth of older people every year, the number of elderly care centres has increased tremendously to cater to the demands of older people to spend their time after retirement in Malaysia. Effective operation and maintenance activities in an elderly care centre can optimise the service life of assets that indirectly lead to well-maintained facilities and provide the occupants with a safe, comfortable, and efficient living environment. Throughout the asset life cycle, operation and maintenance are the most extended phases, with various core activities that determine the financial health of an organisation. Nevertheless, this area remains relatively underexplored in the existing literature, particularly concerning the challenges posed by Malaysia's ageing population by 2030. Accordingly, this study seeks to investigate the issues of operation and maintenance of assets and facilities in elderly care centres. The method used to collect the data is through site observations and interviews in three elderly care centres, one in Perak and two in Selangor. These findings reveal three significant challenges the operators face: safety inside the accommodation, high operation and maintenance costs, and lack of a structured approach to managing the assets and facilities. Finally, the paper ends with implications of the findings that provide directions for future research.